Anthracnose Diseases of Shade Trees - Tisserat, Ned (My University, 1995)
Anthracnose diseases affect a wide variety of shade trees and are common each spring in Kansas. Ash, cottonwood, elm, oak, maple, sycamore, black walnut and other trees are susceptible to injury from this disease.
L763_1995-03
Keywords: L763; Lawn and Garden; Forestry; Environment and Natural Resources; L